1998
DOI: 10.1071/s97076
|View full text |Cite
|
Sign up to set email alerts
|

Effects of spent mushroom substrate on soil chemical conditions and plant growth in an intensive horticultural system: a comparison with inorganic fertiliser

Abstract: Between November 1991 and 1993, 4 consecutive vegetable crops (sweetcorn, cabbage, potato, and cabbage) were grown in Lincoln, New Zealand. The treatments included spent mushroom substrate (SMS, a by-product of the mushroom industry) applications before each crop at rates of 0, 20, 40, or 80 t/ha (moist), both with and without 1 rate of inorganic fertiliser for each crop (120-338, 40-100, 53-100, and 60-114 kg/ha, respectively, of nitrogen, phosphorus, potassium, and sulfur). SMS applications caused a rapid in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
18
0

Year Published

2004
2004
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 30 publications
(18 citation statements)
references
References 0 publications
0
18
0
Order By: Relevance
“…For this reason, passive leaching by rainfall and snowmelt is a method to treat spent mushroom substrates before its use (Guo and Chorover, 2006). Also, different authors have found an initial net immobilisation of nitrogen (Stewart et al, 1998a) or a nitrification inhibition (Maher, 1994;Stewart et al, 1998b), when these waste substrates were used as organic amendments. So, the mineralisation dynamics of spent mushroom substrates in soil needs to be thoroughly evaluated since it is the main process regulating nutrient availability.…”
Section: Introductionmentioning
confidence: 99%
“…For this reason, passive leaching by rainfall and snowmelt is a method to treat spent mushroom substrates before its use (Guo and Chorover, 2006). Also, different authors have found an initial net immobilisation of nitrogen (Stewart et al, 1998a) or a nitrification inhibition (Maher, 1994;Stewart et al, 1998b), when these waste substrates were used as organic amendments. So, the mineralisation dynamics of spent mushroom substrates in soil needs to be thoroughly evaluated since it is the main process regulating nutrient availability.…”
Section: Introductionmentioning
confidence: 99%
“…The water content of the SMS was 41.10% ± 0.17% (n = 10 samples of 10 g each, dried for 48 h at 60 • C), therefore the dosage on dry mass basis was~1.76 kg·m −2 . Dosages for BC and SMS were calculated relative to pot soil surface area (200 cm 2 /4-L pot; 30 g BC and/or 60 g SMS/pot) and are in the range of dosages used in previous studies that improved plant growth (e.g., [24,26,56]). Abutilon theophrasti seeds were germinated in a non-soil growing mix seven days prior to planting.…”
Section: Growth Conditions and Experimental Designmentioning
confidence: 99%
“…However, negative growth responses have occasionally been reported possibly due to high salinity or metal concentration in compost [25]. Mushroom compost has improved fruit yield in several agricultural crops in the relative short term (one growing season) at high dosages (4.0-8.0 kg·m −2 ) [24,26]; however, the effects of mushroom compost on the growth and performance of woody plants/crops have only been minimally investigated [27].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although this compost is no longer economical for growing consecutive mushroom after harvesting of mushroom, mushroom compost is a valuable soil amendments and source of nutrients for field crop production. The organic material with the different C:N ratios and biochemical compositions not only release nutrients at different pace (Azmal et al, 1996) but also provides specific metal binding sites from which metals are difficult to exchange (Stewart et al, 1998). So there is a great need to create awareness for the use of the organic wastes in combinations with fertilizer nitrogen and fly ash to explore its potentialities, discover its complexities, evaluate its behavior, asses its benefits and learn to adapt for greater benefits, profitability and sustainability in large areas and on the more crops.…”
Section: Introductionmentioning
confidence: 99%